STRATEGY OF GROUNDWATER CONTAMINATION MANAGEMENT AT OXBOW AREA OF PANTERIEK VILLAGE, BANDA ACEH MUNICIPALITY - Eva Herlina (JURNAL TEKNIK SIPIL, 2013)
Abstract: Panteriek village is one of the villages located in Lueng Bata sub-district of Banda Aceh that has problem regarding the decline of the groundwater quality. The groundwater contamination is caused by the community activity, resulting domestic waste water channeled to the oxbow area located around the community settlement. Oxbow is a river region which has been cut off its watercourse. The purpose of this research was to make arrangements for groundwater quality management in Panteriek village, Lueng Bata sub-district of Banda Aceh. This research used various methods in accordance with aspects to be investigated, that is, testing the quality of well water belongs to citizens, oxbow and river water, then drawing the contour of the spread of the groundwater flow in research location. The second step was to identify the water usage involving in the usage of groundwater, garbage disposal, environment sanitation, disposal of household wastewater, and physical condition of the wells. The final step was to arrange the strategy plan of groundwater contamination management by using SWOT analysis. From the measurement, it was obtained that the groundwater and oxbow was in Class-C quality category and moderate contamination level. From the groundwater flow contour, it was known that oxbow water filled citizens well. The oxbow and septik tank have contaminated the wells resources. The strategy obtained from SWOT analysis was government institution, along with the community, improving the quality of the groundwater in simple ways. The citizens can implement simple management to increse the quality of well water by applying three methods: aeration, filtration, and disinfection. It is expected that the Local government must  satisfy the sustainability of the water quality reducvement from Water Company to fulfill clean water for Panteriek citizens.Keywords : Groundwater Contamination, Oxbow Area, SWOTAbstrak: Desa Panteriek  adalah salah satu desa di Kecamatan Lueng Bata di Kota banda Aceh  yang mengalami permasalahan mengenai penurunan kualitas air tanah . Pencemaran air tanah  berasal dari aktifitas masyarakat yang menghasilkan air  limbah domestik yang di alirkan ke daerah oxbow yang berada disekitar pemukiman penduduk. Oxbow adalah daerah sungai yang telah ditutup alirannya atau juga disebut dengan sungai mati. Tujuan penelitian ini adalah menyusun langkah-langkah pengelolaan kualitas air tanah di wilayah Desa Panteriek, Kecamatan Lueng Bata Banda Aceh. Penelitian ini diawali dengan melakukan pengujian kualitas air sumur warga, air oxbow dan air sungai untuk mengetahui kualitas air nya, kemudian dilakukan penggambaran kontur penyebaran pencemaran air tanah di lokasi penelitian. Selanjutnya mengidentitifikasi penggunaan air meliputi pemakaian air tanah, pembuangan sampah,  sanitasi lingkungan, pembuangan air buangan rumah tangga, dan kondisi fisik sumur. Terakhir melakukan penyusunan perencanaan strategi pengelolaan pencemaran air tanah di lokasi penelitian  yang menggunakan analisis SWOT (Strengh, Weakness, Opportunity, Threat). Dari hasil pengukuran didapat air tanah dan air sumur berada pada baku mutu kelas C dengan tingkat pencemaran sedang. Dari penggambaran Kontur aliran air tanah diketahui bahwa air oxbow mengisi air sumur warga. Oxbow telah mencemari sumber daya air sumur di lokasi penelitian. Strategi yang didapat dari analisis SWOT adalah  kelembagaan pemerintah bersama-sama masyarakat melakukan perbaikan kualitas air tanah secara sederhana. Warga dapat melakukan pengolahan sederhana untuk memperbaiki kualitas air sumur dengan 3 metoda yaitu aerasi, filtrasi dan desinfeksi. Srategi selanjutnya adalah masyarakat tetap memelihara enceng gondok di kawasan oxbow dan menanam  tanaman akar wangi diperumahan warga untuk mengurangi pencemaran air tanah.Kata kunci : Pencemaran air tanah, daerah oxbow, SWOT.